A Digital Advance for Housing, Land and Property Restitution in War-Affected States: Leveraging Smart Migration. Issue 1 (27th October 2017) - Unruh, Jon; Frank, Emily; Pritchard, Matthew
The large-scale restitution of housing, land and property (HLP) for those dislocated due to armed conflict has significant repercussions for the prospect of return, recovery and durable peace. Failure to adequately engage in restitution and other remedies for displaced populations has demonstrated that the grievances generated usually do not abate, but instead grow, including over generations, to produce subsequent problems, including armed conflict. While advances in transitional justice have supported the development of mass claims processes for HLP in war-affected countries, the current magnitude and complexity of forced dislocation is beyond the ability of conventional techniques to manage in an effective and timely way. This article argues that the current approach for handling massive numbers of HLP claims in postwar scenarios needs a critical upgrade; and describes what such an upgrade could comprise with a set of advanced techniques. These techniques focus on the issues of time, the size and complexity of the problem, new spatial technologies, and the now much greater agency possessed by displaced populations made possible by mobile digital technologies.